I already calculated this
Let a^3 - b^3 = ?
Add on both th side -3a^2b + 3ab^2
a^3 -3a^2b + 3ab^2 -b^3 = ?
-3a^2b+3ab^2
The firs equation is = (a - b)^3
Then,
(a - b)^3 = ? + 3a^2b - 3ab^2
Passing -3a^2b + 3ab^2 to the left side:
But changing the sinal
? = (a - b)^3 + 3a^2b - 3ab^2
? = (a - b)^3 + 3ab ( a - b)
Putting (a - b) as commun factor
? = (a - b).[ 3ab + (a - b)^2 ]
As (a - b)^2 = a^2 - 2ab + b^2
Then,
? = (a - b).[ 3ab + a^2 -2ab +b^2]
? = (a - b).( a^2 + ab + b^2)
I hope this has helped